Prevalence of Metabolic Syndrome and Associated Risk Factors in the United Arab Emirates: A Cross-Sectional Population-Based Study - Ibrahim Mahmoud; Nabil Sulaiman; Nabil Sulaiman (Frontiers Media S.A., 2022)
AimsTo estimate the prevalence of metabolic syndrome (MetS) and its associated risk factors among the United Arab Emirates (UAE) residents.MethodsA cross-sectional population-based study was conducted among adults living in Sharjah and Northern Emirates using the UAE National Diabetes and Lifestyle Study (UAEDIAB) data. Anthropometric measurements and fasting blood samples were obtained. The National Cholesterol Education Program's Adult Treatment Panel III (NCEP/ATP III) guidelines were used to define metabolic syndrome (MetS).ResultsA total of 3,212 subjects (74.1% men, 25.9% women, mean age 39 ± 11.3 years old) were included in this study. The overall prevalence of MetS was 37.4% (32.7% in women and 39% in men). The prevalence was 33.6% in the Emirati population (38.7% in women and 28.8% in men), 34.5% in the Arab non-Emirati population (29.8% in women and 36.3% in men) and 40.7% in the Asian non-Arab population (25.8% in women and 43.1% in men). Age, gender, ethnicity, educational level, marital status and body mass index were positively associated with MetS.ConclusionsThis study indicates a high burden of MetS in the UAE, particularly among Emirati women and Asian non-Arab men. The young adult population in the UAE has a high prevalence of MetS compared to global estimates in the same age group. Aggressive intervention strategies targeting the whole population as well as individuals at a high risk are recommended to prevent the development of cardiovascular diseases.